Remedierede iscenesættelser: – om virtuelle og teatrale verdener - Heinrich, Falk (Peripeti, 2021)
»Can or should we understand MMORPG as theatrical stagings?« Heinrich asks in the article »Remediated stagings.« With the virtual online worlds Second Life and World of Warcraft as examples Heinrich argues that such worlds should not